Formal and Real Power in General Equilibrium - Hans Gersbach; Hans Haller (ETH Zurich, CER-ETH - Center of Economic Research, 2015)
We integrate individual power in groups into general equilibrium models with endogenous group formation. We distinguish between formal power (the say in group decisions) and real power (utility gain from being in groups). Their values will be determined as part of the equilibrium. We find that higher formal power does not necessarily translate into higher equilibrium utility or higher real power. One reason is that induced price changes may offset the groupmember's increased influence. A second reason is that the group may dissolve when a group member gains too much influence, because other members can exercise the option to leave. We also show that maximal real power can be compatible with Pareto efficiency. We further identify circumstances when changes of formal power in one group do not impact on other groups. Finally, we establish existence of competitive equilibria, including equilibria where some individual enjoys real power.
Keywords: D41; D50; D60; 330; Group formation; competitive markets; power; exit